Z-2(1-Z)-2Z=

Simple and best practice solution for Z-2(1-Z)-2Z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Z-2(1-Z)-2Z= equation:


Simplifying
Z + -2(1 + -1Z) + -2Z = 0
Z + (1 * -2 + -1Z * -2) + -2Z = 0
Z + (-2 + 2Z) + -2Z = 0

Reorder the terms:
-2 + Z + 2Z + -2Z = 0

Combine like terms: Z + 2Z = 3Z
-2 + 3Z + -2Z = 0

Combine like terms: 3Z + -2Z = 1Z
-2 + 1Z = 0

Solving
-2 + 1Z = 0

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 1Z = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 1Z = 0 + 2
1Z = 0 + 2

Combine like terms: 0 + 2 = 2
1Z = 2

Divide each side by '1'.
Z = 2

Simplifying
Z = 2

See similar equations:

| 6x^8+4x^8= | | 3(Y-2)-2(Y-6)= | | -15=x^2+8x | | -1/7+Y=5/7 | | 10x^8+3x^6= | | 6=7b-pb | | 50c+349-200=400 | | 28x^2-18x+72=0 | | -2v-22=-8(v-1) | | -2(u+6)=-8u+48 | | -(x+8)(x-9)=-52 | | 9x+12=-6(x+3) | | 22=5(w+6)+3w | | 6(x-4)-2x=-4 | | -10=5(y+8)+5y | | 18+4(3G-7)=-70 | | 64in^2=12.6(h) | | 3x+53=6x+8 | | -5.24=w/8+5 | | 28.8-4v=3.2 | | -14.6=-2.1+x/5 | | -8+w/3=7 | | 585b=868+368b | | 8/3-1/4 | | 585=868+368 | | 1/6d+8/3-1/4=d | | 2x+79=7x+9 | | 2(30)-30=x | | 5y=3x+bforx | | 1/3n-12=10 | | x+1/4=75/7 | | 2/5-5/6 |

Equations solver categories